Disciplinary removal patterns among students with other health impairments and emotional disturbance: A three-year descriptive analysis of IDEA Part B data - Melissa Beck Wells (PLoS ONE, 2026)
Students classified under Other Health Impairment (OHI), a category that includes Attention-Deficit/Hyperactivity Disorder (ADHD), are frequently disciplined in school settings despite ADHD being classified as a neurodevelopmental rather than a behavioral disorder. This study examined patterns of disciplinary removal among students served under the Individuals with Disabilities Education Act (IDEA), Part B, focusing on comparisons between OHI and Emotional Disturbance (ED). Using publicly available IDEA Part B discipline data, a descriptive longitudinal analysis was conducted across three academic years (2019–2020, 2020–2021, and 2021–2022). Percentage-based indicators were analyzed to examine the proportion of students ages 3–21 subject to disciplinary removal by disability category and state. Across all three years, students classified under OHI experienced disciplinary removal at rates comparable to, and in many states exceeding, those of students classified under ED. These patterns persisted despite year-to-year variation associated with the COVID-19 pandemic. Findings are interpreted through IDEA procedural safeguards and DSM-5 diagnostic frameworks, highlighting a potential misalignment between neurodevelopmental disability classification and behavioral support provision. The study discusses how Universal Design for Learning (UDL) may reduce disciplinary risk through proactive design, while emphasizing that individualized behavioral interventions, including Functional Behavioral Assessments and Behavior Intervention Plans, remain legally required when behavior is a manifestation of disability.